The Effect of Motivation, Compensation, and Job Satisfaction an Employee Performance at PT. Bank Anz Indonesia - Shofi Sasmita; Beureukat; Adam Nurkholik; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to determine and analyze the effect of motivation, compensation, and job satisfaction on employee performance at PT. ANZ Bank Indonesia. This type of research data uses descriptive quantitative methods and uses primary data in the form of a questionnaire to 80 respondents in a closed manner at PT. ANZ Bank Indonesia. The data analysis technique uses inferential analysis with multiple linear regression and uses the Statistical Product and Service Solution (SPSS) version 25 program. The results of smultiple linear regression analysis show that the motivation variable (X1) has no positive and insignificant effect on employee performance, compensation (X2) has a positive and significant effect on employee performance, and job satisfaction (X3) has a positive and significant effect on employee performance. From the results of this study, it is expected that PT. Bank ANZ Indonesia can maintain and evaluate deficiencies in Compensation, Motivation, and Work Discipline that can improve Employee Performance.